Functional and symbolic learning in CoPs: Impact on community dynamics - D’Antone, Simona; Cova, Bernard (Management international / International Management / Gestiòn Internacional)

(untitled) (HEC Montréal, 2025)
While learning to be a member was a key theme in early research on communities of practice, subsequent work has focused on the functional dimension of learning. The cultural perspective introduced in this paper allows to consider both the symbolic and functional aspects of learning to participate in a community, and the skills this requires. By observing the social life of two inter-organizational communities of practice (that of financial analysts and that of physicians), we examine the role of totems and rituals in understanding community dynamics. We detail how to study communities of practice using a cultural approach, and we identify practical and managerial implications, including better participation.